(untitled) (LEARNing Landscapes, 2009)
In an attempt to address the gendered achievement gap in writing that exists both nationally and internationally, Gary McPhail conducted a year-long teacher research study focused on the gendered literacy interests of his first grade students and how they responded to a writing curriculum he created that included genres intended to be of interest to both boys and girls. This paper focuses on the experiences of one self-declared "bad boy" in Gary’s class.